Development of symbolic modeling videos containing syair gulung to improve students' social citizenship harmony - Halida Halida; Syawaluddin Syawaluddin; Yogi Damai Syaputra; Zaky Ibrahim Zayn Borneo (Universitas Tanjungpura, 2023)
Based on needs assessments in the field, Guidance and Counseling Teachers need guidebooks and symbolic modeling videos containing interesting and fun local wisdom. Guidebooks and symbolic modeling videos containing Syair Gulung are designed to improve students' social and civic harmony. The composition of rolled poetry lines and symbolic modeling videos can have an effect on changes in students' cognitive and behavior. The aim of this research focuses on producing products, namely guidebooks and Syair Gulung videos. Research and development is hereby adopted from Borg and Gall, then modified according to needs and limitations in the field using seven steps, namely (1) preliminary study; (2) carry out planning; (3) initial product development; (4) initial product validation by assessors; (5) product revision; (6) user testing; (7) final production. The books and videos developed have been validated by three media experts, two Guidance and Counseling experts, two potential users from Guidance and Counseling Teachers and three cultural experts. The research results revealed that the guidebook for implementing group guidance services using symbolic video modeling to improve students' social and civic harmony was declared suitable for use because it met the elements of excellent product acceptability with high validity. Social harmony which is enhanced through symbolic modeling containing rolled poetry consists of four indicators, namely awareness of cultural diversity, tolerance, self-openness and resolving conflicts constructively. This research only extends to testing media experts, cultural experts, guidance and counseling experts, potential users, and product trials on a small scale. It would be better for future researchers to conduct large-scale experimental research to see the effectiveness of this product.